Child work on Platforms. General and Gendered Aspects of YouTubers as Case Study - Shlomit Feldman; Shulamit Almog (Labour & Law Issues)
This paper examines and conceptualizes the economic aspect of young people's activities on the network, focusing on YouTube. We will present YouTube activity and explore how the young population active on the platform perceives it: Is the dominant element in this context play and self-expression for its own sake or generating financial gain? Or is it a hybrid form of activity that embodies both elements?  Are there distinct characteristics that define the play/labor of girls on YouTube and if so, are specific protections needed?  We will argue that, YouTubers' activities resemble a type of platform work that indeed involves an aspect of potential exploitation of minors, and has a gendered dimension – a situation that calls for reforming existing child labor norms to address it. We propose that two principles must be recognized to promote a solution. First, it is important to acknowledgee that YouTuber activity is not just leisure but also work, even when the participants are children and youth below the legal employment age. Second, since this is a form of work, children should not be excluded from participating in these platforms, but should be provided with fair employment conditions and wages. This two-staged recognition could not only address the economic exploitation of children and youth on platform work, but also untangle the connections these platforms create between the economic aspirations of girls and traditional gender norms.